Does reduced‐port laparoscopic surgery for medically uncontrolled ulcerative colitis do more harm than good?. Issue 1 (22nd October 2015) - Homma, Shigenori; Kawamata, Futoshi; Shibasaki, Susumu; Kawamura, Hideki; Takahashi, Norihiko; Taketomi, Akinobu
Abstract: Introduction: Reduced‐port laparoscopic surgery is a novel minimally invasive surgery. However, reduced‐port surgery for ulcerative colitis (UC) remains controversial. Here, we describe the clinical outcomes of single‐incision plus one port laparoscopic surgery (SILS + 1) for medically uncontrolled UC. Methods: Between May 2011 and September 2014, 10 UC patients underwent SILS + 1 port surgery. All procedures were performed with the use of a SILS port and either a 5‐mm or a 12‐mm port placed at the planned ileostomy site. Results: The median age of patients was 32 years (range, 22–53 years). Six patients underwent two‐stage SILS + 1 port restorative proctocolectomy with ileal pouch‐anal anastomosis, two patients underwent SILS + 1 total proctocolectomy, and the remaining two patients underwent SILS + 1 subtotal colectomy with subsequent three‐stage SILS + 1 ileal pouch‐anal anastomosis. The median operative time was 363.1 min (range, 253–465 min) and the median estimated blood loss was 29 mL (range, 0–100 mL). There were no conversions or additional ports required. Two patients previously underwent SILS + 1 subtotal colectomy, and in one of those patients, SILS + 1 ileal pouch‐anal anastomosis was performed successfully 6 months after the previous surgery. There were no intra‐abdominal adhesions, and no extra wounds were necessary because the previous stoma site had been used to access the SILS port. The median postoperative period was 24 months, during which five patients had their ileostomies closed. No patients reported occasional minor daily soiling or the need to wear a pad. Conclusion: Reduced‐port laparoscopic surgery for medically uncontrolled UC is a feasible and safe procedure when performed by skilled surgeons.